SME managers' causal beliefs on HRM as success factor of the firm - Viitala, Riitta; Vesalainen, Jukka; Uotila, Timo-Pekka (Taylor and Francis, 2020)
Normative human resource management (HRM) literature offers an abundant and sophisticated picture on the ideal HRM practices leading to certain positive HRM outcomes. Explanatory empirical research has also confirmed positive relationships between HRM and organizational performance. This study approached SMEs HRM from a different perspective. We studied how HRM manifests itself in managerial perceptions concerning the important drivers of firm performance. A research strategy was followed that addressed HRM as it naturally manifests itself within holistic managerial thinking. A causal mapping technique was used to elicit causal maps for 37 CEOs of industrial SMEs. The findings indicate that HRM has a varying role as a performance driver in managers’ causal beliefs. As the main result we propose a categorization of SME managers’ thinking on HRM consisting of four types with different level of conceptual richness and cognitive complexity: Managers with mature, narrow, scattered and vague causal beliefs of HRM as a driver for organizational performance.
Keywords: Human resource management; managerial cognition; small and medium enterprises; success factors of the firm; Henkilöstöjohtaminen